'Act Out Justice': reflective collaborative inquiry on theatre for social change youth programming. Issue 3 (3rd May 2020) - Horn, Elizabeth Brendel; Caine, B.; Katsadouros, M.; Freeman, E.
ABSTRACT: This study outlines and analyzes the effectiveness of a reflective collaborative inquiry model developed for the programmatic and curricular revisions of 'Act Out Justice' (AOJ), a theatre for social change youth program through a partnership between Orlando Repertory Theatre and the University of Central Florida. The authors identify a nine-step process for collaborative teams utilizing a fusion of personal narrative, reflection, and dialogue. This account guides the reader through the AOJ reflection and revision process, articulating how the process revealed four concrete programmatic and curricular changes. The paper provides a model for collaborative reflective inquiry applicable to collaborative teams working with youth.